Peran Manajemen Humas dalam Meningkatkan Mutu Pendidikan di Sekolah Islam Menurut Al Qur’an dan Hadits - Kotimah, Khusnul; Fauji, Imam (Asian Journal of Islamic Studies and Da'wah, 2025)
This study aims to analyze the role of public relations management in improving the quality of education in Islamic schools based on the perspective of the Qur'an and Hadith. The quality of education is one of the main indicators in the development of Islamic educational institutions, which requires support from various parties, including the community. Public relations management serves as a strategic link between the school and the community to build trust, collaboration and sustainable support. The research method used is Systematic Literature Review (SLR) with a descriptive qualitative approach. Data were analyzed based on Islamic principles listed in the Qur'an and Hadith, as well as public relations practices in educational institutions. The results showed that effective PR management can strengthen the positive image of the school, increase community participation, and promote Islamic values widely. In addition, principles such as deliberation, transparency and shared responsibility are key in building harmonious relationships between schools and communities. In this study, we will discuss the role of public relations management based on Islamic values that has a significant contribution in creating superior education quality in Islamic schools. Thus, this research is expected to provide guidance for Islamic educational institutions to optimize public relations management in improving education quality and relevance.